Answer:
infinite solutions
Step-by-step explanation:
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13
Ditribute
-15x -10 -x +3 = -16x - 20+13
Combine like term
-16x -7 = -16x -7
Add 16x to each side
-16x+16x -7 = -16x+16x-7
-7 =-7
This is always true so we have infinite solutions.
answers
All real numbers are solutions
step by step
5(−3x−2)−(x−3)=−4(4x+5)+13
Step 1: Simplify both sides of the equation.
5(−3x−2)−(x−3)=−4(4x+5)+13
5(−3x−2)+−1(x−3)=−4(4x+5)+13(Distribute the Negative Sign)
5(−3x−2)+−1x+(−1)(−3)=−4(4x+5)+13
5(−3x−2)+−x+3=−4(4x+5)+13
(5)(−3x)+(5)(−2)+−x+3=(−4)(4x)+(−4)(5)+13(Distribute)
−15x+−10+−x+3=−16x+−20+13
(−15x+−x)+(−10+3)=(−16x)+(−20+13)(Combine Like Terms)
−16x+−7=−16x+−7
−16x−7=−16x−7
Step 2: Add 16x to both sides.
−16x−7+16x=−16x−7+16x
−7=−7
Step 3: Add 7 to both sides.
−7+7=−7+7
0=0